Rendimento de carne do caranguejo-uçá, Ucides cordatus (Linnaeus, 1763) (Crustacea, Brachyura, Ucididae) - Pinheiro, Marcelo Antonio Amaro [UNESP]; de Souza, Caroline Araújo [UNESP]; Borba, Hirasilva [UNESP] (My University, 2015)
Specimens of Ucides cordatus were captured from September 1998 to September 2000 in mangroves from Iguape, SP, Brazil (24º41’25”S - 47º27’48”W) and analyzed by sex, biological period (reproductive, October to March; and non-reproductive, from April to September) and size. The meat yield of each corporal structure, and the residuals were quantified. Each crab was measured (carapace width) with a vernier caliper (0.05 mm) and their corporal structures weighed with an analytic scale (0.0001 g). Biometric variables were previously tested (normality and homoscedasticity) with indication of a statistical parametric procedure (ANOVA) at 5% significance level. Males had higher wet weight than females, the same occurring when their corporal structures were compared (p<0.05). The meat yield in males was of 25.4%, a little above than what was registered in females (21.1%); meat yield hierarchy among corporal structures was very similar between sexes and biological periods, but differing in relation to chelipeds, which were bigger in males. During the reproductive period males had a bigger meat yield due to their size when compared to males of non-reproductive period, as well as with females independently of their biological period. The expressive meat yield in males can be explained by the positive allometric growth of the chelipeds after puberty molt when this structure grows proportionally more than the body itself, accounting for 40% of the total wet weight in this gender.
Meat yield of the mangrove crab, Ucides cordatus (Linnaeus, 1763) (Crustacea, Brachyura, Ucididae)
Keywords: Biometry; Crab; Fishery resource; Meat extraction; Morphology; Reproduction